ATTRIBUTE SELECTION F INDONESIAN TELEMATIC SERVICES MSMEs FEASIBILITY ASSISTANCE, USING AHP - Eneng Tita Tosida; Kudang Boro Seminar; Yeni Herdiyeni (Jurnal Ilmiah Kursor, 2015)
The assistance program had not absorbed optimally yet for telematics Micro Small Medium Enterprises (MSMEs). One of the reasons was the data of telematics MSME which still separated in the several institutions. This research aimed to selection of assistance feasibility attributes using Analytical Hierarchy Process (AHP) based on National Socio-Economic Survey (Susenas) data. This data attributes conformed to the criteria of assistance feasibility which was implemented among by Ministry of Cooperative, Small and Medium Enterprises (SMEs), and related institutions. The attributes involved the characteristic of technology, economics, human resources, partnerships, obstacles, prospect and other common conditions. The process of data preparation was needed involving cleaning, discretization, description and transformation of data. The AHP technique aimed to produce rankings and the value of attributes. The finding of this research showed that start-up essence and technology factors became the crucial attributes in the feasibility assessment. The other factors were the economy, human resources, partnerships and development planning. The findings of this research had given the new innovations; in addition of the scope of related substance Telematics Service MSMEs which was still studied limitedly, and the selection technique of assessment feasibility attributes based on Susenas data.